Evaluation of the Performance of Different Traps for Sampling Usutu and West Nile Viruses and Mosquito (Diptera: Culicidae) Vectors in Senegal. Issue 1 (14th August 2018) - Diallo, Diawo; Ndiaye, El Hadji; Fall, Gamou; Ba, Yamar; Faye, Ousmane; Dia, Ibrahima; Diallo, Mawlouth
Abstract: An efficient trapping tool is one of the most important factors in surveillance and research on arboviruses and their vectors. In the current study, we tested the efficiency of several traps for sampling West Nile (WNV) and Usutu (USUV) viruses and their vectors in Senegal during 2013. A total of 15, 527 mosquitoes (Diptera: Culicidae), 94.3% females, were collected. Among the known arbovirus vectors, Mansonia uniformis (Theobald) (Diptera: Culicidae) was the most abundant (46.5%), followed by Culex poicilipes Theobald (Diptera: Culicidae) (19.5%), Culex tritaeniorhynchus Giles (Diptera: Culicidae) (8.0%), and Culex neavei Theobald (Diptera: Culicidae) (6.1%). The geometric means of these vectors varied by trap, location, and height. WNV was isolated from Cx. neavei and Cx. tritaeniorhynchus collected by pigeon-baited traps within the canopy, CO2 -CDC traps within the canopy and at the ground. USUV was isolated only from Cx. neavei collected by pigeon-baited traps and CO2 -CDC traps within the canopy. Therefore, for each study, the trap to be chosen will depend on the mosquito species and virus targeted.